In for winter, out for spring - Adoff, Arnold; Pinkney, Jerry (San Diego : Harcourt Brace Jovanovich, 1990)
This collection of poems, told from the perspective of a young girl, celebrates family life throughout the yearly cycle of seasons.
NP
Keywords: Seasons -- Juvenile poetry; Children's poetry, American; American poetry; Seasons -- Poetry; Family life -- Poetry